Effect of social media usage on the lifestyles of youth - Azlina Abdullah; Zurinah Tahir; Nur Hafizah Yusoff; Filyntiana Tenge Andrew (Penerbit Universiti Kebangsaan Malaysia, 2022)
Youth today are inclined to use social media as a means of transmitting knowledge through a variety of social networks and media. The use of social media can indirectly engender a positive effect by promoting desirable changes in morals and culture among users. Nevertheless, social media can also be misused, leading to negative outcomes affecting youth and the general community. This study was undertaken to determine the effect of social media usage on the lifestyles of youth. A quantitative approach was employed, with data collected from 82 students of the Universiti Kuala Lumpur-Malaysia France Institute (UniKL-MFI), Bangi, Malaysia. The participants ranged in age from 19 to 35. The questionnaire-survey focused on the impact of social media on youths who utilized this facility on a daily basis. Hence, the effects resulting from social media usage have been shown to influence the lifestyles of youths in terms of their activities, interests and opinions. The study results showed that the lifestyles of youths were impacted in different ways and to varying degrees. At the top of the list was the influence of foreign cultures and trending topics, followed by the adoption of virtual social interaction, freedom of expression, acquisition of contacts unknown to them, health issues, privacy and security issues, and the preference of electronic gadget-based games over outdoor activities.